Osthole alleviates MPTP-induced Parkinson's disease mice by suppressing Notch signaling pathway. (2nd September 2019) - Wang, Yu; Zhou, Yong; Wang, Xiang; Zhen, Fei; Chen, Rui; Geng, Deqin; Yao, Ruiqin
Abstract: Objectives: Parkinson's disease (PD) is an age-related neurodegenerative disease characterized by motor dysfunctions. Dopaminergic neuron loss, inflammation and oxidative stress responses play key roles in the pathogenisis of PD. Osthole (Ost), a natural coumarin derivative, isolated from various herbs such as Cnidium monnieri (L.), has anti-inflammatory, anti-apoptotic and anti-oxidative stress properties. However, whether it has effects on PD is unknown. Methods : In this study, mice were subjected to 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) injection to induce PD symptoms, and treated with osthole. Stepping and cylinder tests were performed to determine their motor function. Immunohistochemical and immunofluorescence staining were performed to detect tyrosine hydroxylase (TH) and ionized calcium binding adaptor molecule 1 (Iba-1). The expression levels of inflammatory cytokines and oxidative stress factors were detected by qPCR and ELISA. Notch signaling pathway was investigated by western blot. Results : We found that injection of MPTP induced motor deficits in mice, enhanced the loss dopaminergic neurons and the activation of microglia, increased inflammatory and oxidative stress responses, and inhibited Notch signaling pathway. Osthole treatment suppressed theses MPTP-induced alterations. Conclusion : In conclusion, osthole attenuates PD symptoms by suppressing Notch signaling pathway.